2018
DOI: 10.3390/rs10020345
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Insufficient Observations on the Monitoring of Short- and Long-Term Suspended Solids Variations in Highly Dynamic Waters, and Implications for an Optimal Observation Strategy

Abstract: Coastal water regions represent some of the most fragile ecosystems, exposed to both climate change and human activities. While remote sensing provides unprecedented amounts of data for water quality monitoring on regional to global scales, the performance of satellite observations is frequently impeded by revisiting intervals and unfavorable conditions, such as cloud coverage and sun glint. Therefore, it is crucial to evaluate the impacts of varied sampling strategies (time and frequency) and insufficient obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Long-term series-calibrated OBS measurements were also carried out at two stationary stations (A1 and K1 in Figure 1) in 2007 and 2008 and these were treated as the "ground truth" for continuous calibration of OBS data. More details on the collection of SS can be found in [50].…”
Section: High Frequency Ss Samplesmentioning
confidence: 99%
“…Long-term series-calibrated OBS measurements were also carried out at two stationary stations (A1 and K1 in Figure 1) in 2007 and 2008 and these were treated as the "ground truth" for continuous calibration of OBS data. More details on the collection of SS can be found in [50].…”
Section: High Frequency Ss Samplesmentioning
confidence: 99%
“…The optimal sampling scale is highly related to the spatial and temporal characteristics of ground targets. Low or high scales will lead to insufficient information or information redundancy, which will influence the analysis and interpretations of satellite remote sensing [8,18].…”
Section: Determination Of Optimal Spatial and Temporal Scalesmentioning
confidence: 99%
“…Satellite remote sensing provides unprecedented opportunities to monitor vegetation dynamics, including peak foliage coloration at large scales, because of the various spatial and temporal coverages of satellite observations [8]. Over the past decade, various methods based on satellite remote sensing data have been widely used to monitor vegetation phenology [9].…”
Section: Introductionmentioning
confidence: 99%
“…Important ocean color sensors orbiting the earth include the Moderate Resolution Imaging Spectroradiometer (Terra/Aqua MODIS, 1999-present), the US Visible Infrared Imager Radiometer Suite (VIIRS, 2011-present), the Ocean and Land Color Instrument (Sentinel-3A OLCI, 2016-present) and the Korean Geostationary Ocean Color Imager (GOCI, 2010-present). Prepared to launch are several other ocean color sensors, including the Chinese HY-series satellites and NASA PACE mission [7,8]. Ideally, ocean color remote sensing unprecedentedly provides data for water quality properties at various spectral, temporal and spatial scales [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Observations should preferably be taken every 30 min to 1 h [24], while inappropriate sampling frequencies and/or times could introduce large biases and eventually lead to unscientific decisions in water management. Previous studies have indicated that inappropriate sampling time and frequency in water quality monitoring have led to statistical errors larger than 50% [7,25,26]. The facts of missing data from CZCS remote sensing resulted in a root mean-square error (RMSE) of 8% for annual mean chlorophyll concentrations, and a RMSE of 33% when determining the peak chlorophyll values [18].…”
Section: Introductionmentioning
confidence: 99%